Diagnosis and Treatment of Dermatomyositis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The impact of duration of untreated symptoms in children with juvenile dermatomyositis (JDM) on clinical and laboratory findings at diagnosis was studied in 166 patients enrolled in the National JDM Research Registry and examined at Children's Memorial Hospital, Northwestern University; Loyola University; and University of Chicago, Chicago, IL; and other centers in the US.